Analisis Problematika Akad Nikah Virtual Perspektif Empat Mazhab - Rafli, Mohammad; Misbaahuddin Asyuari, A. Zaeini (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2023)
Digitalization has changed many aspects of human life, including marriage. The purpose of this study is to analyze the problems of virtual marriage practice according to the views of four schools. This research uses the library research method through a normative legal approach (Islamic law). The results of this study are as follows: (1) Connectivity imbalance causes loss of ijab and kabul networks. The Hanafiyyah and Hanbaliyyah schools considered the marriage contract valid, the Shafi'iyyah and Malikiyyah schools invalid. (2) The occurrence of speculative elements that cause one of the brides-to-be not to meet the requirements, scholars of the four schools of thought agree that the marriage contract is invalid. (3) The loss of audio from one or both parties that causes the witness and the contractor to be unable to hear each other. According to the three schools (Hanafiyyah, Shafi'iyyah, and Hanbaliyyah), the marriage contract is invalid. According to the Malikiyyah school, the law is valid. (4) Visual loss (image) that causes the witness to be unable to see the party performing the contract. According to the Hanafi school, Hanbaliyyah and Malikiyyah marriage contracts are valid. At the Shafi'iyyah School, the contract is invalid. (5) Regulations issued by the Ministry of Religion regarding the impermissibility of virtual marriage contracts, if the marriage contract has met the requirements and harmony, the validity of the marriage contract is not affected by regulations set by the government.